Contrastive analysis of adolescent learner interlanguage in asynchronous online communication: A keyness approach. (December 2015) - Lin, Yen-Liang
Abstract: Online communication provides learners of English with opportunities to interact with native speakers across geographical boundaries. While there is a burgeoning field of research which looks at computer-mediated communication (CMC), few studies have employed a keyness approach to the analysis of interlanguage of adolescent learners. This study reports on a corpus analysis of samples of asynchronous online discourse between a group of British and Taiwanese adolescents, with the aim of exploring the significant differences in the use of grammatical categories between the two groups of participants. Keyness analysis (Rayson, 2008) at the part-of-speech level highlights the linguistic features which deserve particular attention. Specifically, it reveals the grammatical categories that occur unusually frequently or unusually infrequently in the English learners' discourse when compared with the language used by the native speakers of English in the same sample. The research findings demonstrate the pedagogical merit of keyness analysis and thus help in the design of courses for adolescent online interaction.